Correction: Probing keto–enol tautomerism using photoelectron spectroscopy. Issue 1 (6th December 2017) - Capron, Nathalie; Casier, Bastien; Sisourat, Nicolas; Piancastelli, Maria Novella; Simon, Marc; Carniato, Stéphane
Abstract : Correction for 'Probing keto–enol tautomerism using photoelectron spectroscopy' by Nathalie Capron et al., Phys. Chem. Chem. Phys., 2015, 17, 19991–19996.